(untitled) (Research, Society and Development, 2023)
Epidemiological studies on tuberculosis in Brazil are essential to identify current trends and potential factors that contribute to the persistence of the disease as a public health problem in the country. General objective: To analyze the current situation of epidemiological cases of tuberculosis in Brazil, considering trends, challenges and possible solutions for prevention and reduction in the number of cases. Materials and methods: Quantitative study of a documentary, statistical and retrospective nature through collection and comparison of data from individuals diagnosed with tuberculosis reported in Brazil, through DATASUS, which is the health information system of the Brazilian Ministry of Health, responsible for collecting, processing and make health data available in the country. Final considerations: It is necessary to strengthen primary health care as a gateway and coordinator of care for patients with tuberculosis, as well as promoting intersectoral actions that guarantee the social and human rights of people affected by the disease.